Nanocompósito de PP/PP-g-AM/argila organofílica: processamento, propriedades mecânicas, termo-mecânicas e de permeação de gás - Morelli, Fernanda Cathusca (2009)
The aim of present work was developing nanocomposites of polypropylene (PP) with organoclay (MMT) in the presence of a compatibilization agent (PP-g-MA) in the melt state. The masterbatch of PP-g-MA and organoclay was prepared in a mixer with high shear rate and then cryogenically frozen and ground. The nanocomposites were prepared with 1.5%, 2.5%, 5% and 7.5% (w/w) of organoclay into PP in a twin screw extruder. In the all case it was maintained the ratio of 1:3 organoclay/PP-g-MA. The morphology and structure of the nanocomposites were evaluated by their thermo-mechanical properties, tensile strain and permeability to water vapor and oxygen. The analysis of XRD showed a marked decrease the in peak intensity referring to the pure organoclay for all nanocomposites. The SEM / FEG micrographs revealed the morphology of the surface for all sample. It was observed the complete dispersion of organoclay into polymeric phase and the structure seen was like a rod with some mixed clusters. While the micrographs of TEM showed the formation of nanocomposites with high intercalation for 1.5% and 2.5% of organoclay. The TGA analysis demonstrated an increase in the temperature of degradation (2% loss of mass) of 29°C for the sample of 1.5% of organoclay. The DSC curves did not show any influence of organoclay in the values of Tf for ΔHf and nanocomposites. The DMTA analysis showed an improvement for all parameters examined (on the storage modulus, change the temperature of phase transition α 'and HDT) once more for the sample of 1.5% of organoclay. The permeability to water vapor was effective, especially for the sample of 1.5% of organoclay, where the reduction was of 43% lower than extruded PP. However, the permeation of O2 didn t present the same improvement for the nanocomposites studied in comparison to the water vapor permeation.